Pricing strategies for capitated delivery systems - Gruenberg, Leonard (CENTERS for MEDICARE & MEDICAID SERVICES, 1986)
This article discusses alternative methods for establishing a fairer pricing mechanism for Medicare recipients who enroll in health maintenance organizations and other competitive medical plans. The current method, based upon the adjusted average per capita cost, is inadequate because it fails to adjust premium levels for differences in health status; it establishes undesirable incentives that may lead to underservice, and it is tied to costs in the fee-for-service system. Alternative methods would incorporate health status, have Medicare share the risk with HMO's, and base payment on HMO experience.